Empowering Older Women in Malaysia: Understanding Their Health Care Demand (Journal of Governance and Development (JGD), 2014)
Understanding factors that affect health care demand by elderly women is vital for a health system to be more supportive towards women’s empowerment. This paper presents the medical care utilization of the elderly women; identify the existence of income-related inequity in health care utilization and the role of living arrangements of the elderly on health care utilization among the elderly women in Kedah State. A total number of 202 of respondents aged 62 to 95 were interviewed face-to-face using a structured questionnaire. The Probit and Poisson model were used in estimating the demand equation. It is found that income, after controlling for other socioeconomic and health related factors, is not statistically significant in affecting the likelihood of doctor visits, and the frequency of the visits. The role of living arrangement, as measured by marital status and the number of individual aged 18 and over living together is also not significant in both models. This result suggests that older women in the area of study can somehow make independent decisions regarding their health care demand, which demand should ideally base on health status rather than not other factors.